Cytotoxicity and antimicrobial activity of synthetic peptides alone or in combination with conventional antimicrobials against fish pathogenic bacteria - Assane, I. M. [UNESP] (2021)
Aims: This study aimed to evaluate the in vitro cytotoxicity and efficacy of synthetic host defence peptides (HDPs), alone or in combination with florfenicol (FFC), oxytetracycline (OTC) or thiamphenicol (TAP), against different pathogenic bacteria isolated from diseased fish. Methods and Results: Solid-phase synthesis, purification and characterization of several HDPs were performed manually, using the fluorenylmethyloxycarbonyl protecting group in different resins and via high-performance liquid chromatography-mass spectrometry, respectively. The in vitro cytotoxicity and antimicrobial activity of HDPs, FFC, OTC and TAP against Nile tilapia red blood cells (RBCs) and relevant fish pathogenic bacteria (Aeromonas, Citrobacter, Edwardsiella, Streptococcus, Lactococcus and Vibrio) was determined using the haemolysis assay and broth microdilution method, respectively. The checkerboard assay was used to evaluate the synergy between the most active HDPs and other antimicrobials against the tested strains. MUC 7 12-mer, FFC, OTC and TAP were not cytotoxic to Nile tilapia RBCs, in all tested concentrations. LL-37, (p-BthTX-I)2 and Hylin-a1 were not cytotoxic at concentrations up to 78·13, 19·53 and 9·77 μg ml−1, respectively. HDPs demonstrated potent antimicrobial activity (minimum inhibitory concentration ≤31·25 µg ml−1) against Aeromonas jandaei (KR-12-a5), Citrobacter freundii (Kr-12-a5; (p-BthTX-I)2; LL-37; and Hylin a1), Streptococcus agalactiae (Hylin a1; (p-BthTX-I)2 and LL-37), Lactococcus garviae (Hylin a1), and Vibrio fluvialis (KR-12-a5). The combinations of (p-BthTX-I)2 with TAP and LL-37 with FFC showed synergistic activity against C. freundii (fractional inhibitory concentration index of 0·25 and 0·50, respectively). Conclusions: Synthetic HDPs have the potential as a good treatment option for bacterial diseases in aquaculture. Significance and Impact of the Study: The in vivo effectiveness of synthetic HDPs such as KR-12-a5; LL-37; (p-BthTX-I)2 and Hylin a1 can be tested alone or in combination with conventional antimicrobials as a treatment option to reduce the use of antimicrobials in aquaculture.